1995
DOI: 10.1161/01.str.26.6.919
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Stroke Incidence Trends From the 1970s Through the 1980s in East Germany

Abstract: An increase in stroke incidence was detected that can be associated with a deteriorating risk factor profile in the East German population and, in particular, with hypertension in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
4
15
0
1
Order By: Relevance
“…Mostly, the decline in stroke mortality is reported, [3][4][5][6]8 and some centers even show a trend of increasing stroke incidence. 2,6 In the community-based stroke registry in Germany, 2 the increasing incidence rates were explained by unfavorable changes in the risk factor profile, especially concerning blood pressure. The latest comprehensive information on major health indicators in Estonia is available from WHO databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly, the decline in stroke mortality is reported, [3][4][5][6]8 and some centers even show a trend of increasing stroke incidence. 2,6 In the community-based stroke registry in Germany, 2 the increasing incidence rates were explained by unfavorable changes in the risk factor profile, especially concerning blood pressure. The latest comprehensive information on major health indicators in Estonia is available from WHO databases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, in many population groups, concerning stroke time trends, have been published. [1][2][3][4][5][6][7][8] The design of studies mentioned above differ remarkably: registry-based, 2,4,7 hospital-based, 1 data from official statistics, 3,5,8 or cases from limited age groups. 1,2,3,6 All of these results are valuable but cannot be extrapolated to the whole population at risk of stroke, and the described variations in mortality and incidence between different regions and time periods may be mistaken for methodological biases.…”
mentioning
confidence: 99%
“…2,[4][5][6][7] Earlier studies concluded that the decline in stroke mortality was mainly, but not only, due to the decreased incidence of cerebrovascular complications linked to primary prevention measures, especially the detection and treatment of hypertension. Although there was no reduction evidenced in some developed nations, as shown in Table 1, [8][9][10][11][12][13][14][15][16][17][18][19][20] it may be speculated that hypertension treatment has contributed to the decline in stroke mortality, in particular by reducing the severity of acute stroke. 18 Better emergency medical care may also have led to a decrease in casefatality rate.…”
Section: Mortalitymentioning
confidence: 99%
“…Modifiable risk factors (see in Table 2) 23 have been extensively reviewed and the predominant role of hypertension is underlined by all the epidemiological studies. [23][24][25] Hypertension increases the risk for transient ischaemic attacks 26 as well as the incidence of any type of stroke 24 including ischaemic stroke and focal (Harmsen, 1992) 10 No change 1971-1987 Framingham Study 11 No change 1953-1983 New Zealand (Bonita et al, 1993) 12 No change 1981-1991 Hawai (Kagan, 1994) 13 Decrease 1969-1988 China (Cheng et al, 1995) 14 Decrease 1986-1990 East Germany (Eisenblätter, 1995) 15 Increase 1972-1980 Finland (Tuomilehto, 1996) 16 Decrease 1983-1992 Minnesota (Brown et al, 1996) 17 Increase 1950-1989 Portland (Barker et al, 1997) 18 No change 1967-1985 Minnesota (Shahar, 1997) 19 intracerebral haemorrhage. 27 Data from the Framingham Heart Study show that hypertensive subjects have a three-fold greater risk of stroke than normotensive individuals and those with borderline hypertension have a 50% greater risk.…”
Section: Mortalitymentioning
confidence: 99%
“…[3][4][5] Stroke incidence also appeared to decline in the 1960s and 1970s in the United States, 6,7 Asia, 8 and Europe, 9 -11 but this latter decline has also leveled off, and most studies during the 1980s and 1990s have shown either no change [12][13][14][15][16] or more commonly an increase in age-and sex-adjusted incidence. [17][18][19][20][21][22][23][24][25][26] In contrast, UK stroke mortality rates based on death certification have declined steeply in recent decades. 2,27 The decline in the UK appears to be consistent with a 40% decline in population-based stroke incidence and mortality in Oxfordshire, UK, between 1981 to 2004 and 2002 to 2004, 28 but national mortality data could have overestimated the time trends in the UK as a whole because of changes in the practice of death certification.…”
mentioning
confidence: 99%